2012
DOI: 10.1111/j.1447-0594.2011.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective prevention of cardiovascular disease and diabetes‐related events with atorvastatin in Japanese elderly patients with type 2 diabetes mellitus: Adjusting for treatment changes using a marginal structural proportional hazards model and a rank‐preserving structural failure time model

Abstract: Aim:To assess the preventive effect of atorvastatin on cardiovascular disease and on diabetes-related events in elderly type 2 diabetic patients enrolled in the Japanese Elderly Diabetes Intervention Trial (J-EDIT).Methods: Data were obtained from 1173 patients aged 65-84 years who were enrolled in the J-EDIT. Patients were followed prospectively for 6 years to determine the effects of atorvastatin on serum cholesterol levels, and cardiovascular and diabetes-related events. Because the study protocol allowed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
(129 reference statements)
0
17
0
Order By: Relevance
“…The mean average age of the subjects by study (for which age data were available) ranged between 44 and 74.9 years. Thirteen studies included only patients with type 2 diabetes mellitus [ 2 , 3 , 10 , 11 , 17 19 , 21 , 27 30 , 33 ], while 3 studies included only patients with type 1 diabetes mellitus [ 13 , 20 , 24 ]. The average time since diagnosis of diabetes ranged between 4 and 26 years.…”
Section: Resultsmentioning
confidence: 99%
“…The mean average age of the subjects by study (for which age data were available) ranged between 44 and 74.9 years. Thirteen studies included only patients with type 2 diabetes mellitus [ 2 , 3 , 10 , 11 , 17 19 , 21 , 27 30 , 33 ], while 3 studies included only patients with type 1 diabetes mellitus [ 13 , 20 , 24 ]. The average time since diagnosis of diabetes ranged between 4 and 26 years.…”
Section: Resultsmentioning
confidence: 99%
“…This statin also improves leg artery stiffness in type 2 diabetics [Shinohara et al 2005], and appears to reduce the risk of CV and diabetes-related events in elderly Japanese patients with type 2 diabetes [Shinozaki et al 2012]. Atorvastatin does not improve endothelial function, however, in type 2 diabetic patients with average cholesterol levels and no prior CV disease [Tantikosoom et al 2005], and it does not prevent new-onset diastolic dysfunction in a rat model of insulin resistance [Chen et al 2007].…”
Section: Introductionmentioning
confidence: 98%
“… Concomitant medication What is the effect of use of beta blockers, diuretics, and statins on onset of Type 2 diabetes? MSM with IPW [ 3 ] Use of statins and diuretics found to increase risk of diabetes onset Shinozaki (2012) [ 27 ] Diabetes Effect of intensive (target HbA1c 6.9 or less, BMI < 25, BP < 130/80) vs conventional treatment (no target levels) strategies for type 2 diabetes in elderly patients on risk of morality, cardiovascular events and other diabetes related endpoints Concomitant medication Is there a preventative effect of atorvastatin on cardiovascular disease and on diabetic vascular complications? MSM with IPW, structural nested failure time models with g-estimation [ 3 , 53 ] Atorvastatin estimated to be protective against both cardiovascular events and diabetes related events, though confidence intervals for cardiovascular events were very wide.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the other studies in cardiovascular disease [ 23 25 ] and the mental health application [ 26 ] also used MSMs with IPW. Finally, a study by Sinozaki et al [ 27 ] investigated the effect of atorvostatin on various cardiovascular outcomes (including low-density lipoprotein (LDL) cholesterol, composite cardiovascular event endpoints, diabetes-related endpoints) by using both MSMs with IPW and g-estimation of structural nested models. The authors found that both methods produced relatively similar results for all outcomes examined.…”
Section: Resultsmentioning
confidence: 99%